The Changing of Students' Language and Behaviour by the Intensity of Intercultural Communication on Social Media: A Case Study in ELT Class - Supriadin Supriadin; Umar Umar (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
This research conducted based on the phenomon on the languages and behaviours are showed by the students when they interact with their friends, teachers, and stafs at school. This research aims to find out the changes of students’ language and behavior  in relation with the intensity of intercultural communication using social media. This research had been done in one of Senior High Schools in Mataram especially to the third grade students of science and social department. In getting the data, this research applied observation, interview, and questionnaire. It found that the intensity of exchange culture information by using social media has influenced most teenager today. Firstly, the students tend to use their language by using a kind of “Alay language” when they interact with their friends or even with their teachers whether inside or outside of the classroom. Secondly, the intensity of exchange culture information by using social media could help students to finish their school tasks. They work cooperatively with their friends in small groups. They are able to find out the information they need to present cultural celebrations and how something happens in less than fifteen minutes. This intercultural communication could also help them to build up their awareness of cultural differences among them. However, this intensive exchange of cultural information could also lead students to prefer to communicate with their network friends to friends in their school and home environment. Moreover, the students are likely becoming less sensitive towards their friends’ problems. In addition, the intensive of exchange of culture information by using social media could lead them to the model of thinking which is likely to force their arrogances and egoism.